Project-Based Learning: Enhancing EFL Students’ Speaking Skill through Vlog - Wienda Febriyanti Nugroho; Mirjam Anugerahwati (Graduate School of Universitas Negeri Malang, 2019)
Abstract: The purpose of this classroom action research is to enhance the students’ speaking skill using Project-Based Learning through Vlog and looking at their speaking performance in the teaching learning process using PBL through Vlog. Eleven students of vocational students in Indonesia were taken as research subject exposed to the treatment of PBL through Vlog in one cycle. The result of this study showed that after the students were taught by using PBL through Vlog, the eleven students successfully met the criteria of success. The use of PBL through Vlog enhanced the students’ fluency, grammatical accuracy, pronunciation, vocabulary, and content.Abstrak: Tujuan dari penelitian tindakan kelas ini adalah keterampilan berbicara menggunakan Project-Based Learning melalui pembelajaran dan proses belajar mengajar menggunakan PBL melalui Vlogs. Sebelas siswa siswa kejuruan di Indonesia diambil sebagai subjek penelitian untuk pengobatan PBL melalui Vlog dalam satu siklus. Hasil penelitian ini menunjukkan bahwa siswa terpenuhi oleh kriteria kesuksesan. Penggunaan PBL melalui Vlog meningkatkan kelancaran siswa, akurasi tata bahasa, pengucapan, kosa kata, dan konten.